A review of coir fibre and coir fibre reinforced cement-based composite materials (2000–2021). (1st March 2022) - Wang, Bo; Yan, Libo; Kasal, Bohumil
Abstract: This paper provides a comprehensive review on the research of coir fibre and coir fibre reinforced cementitious composite (CFRC) in the past 20 years. In the first part, the extraction process, morphology, density, chemical composition, and tensile performance of coir fibres are discussed. Then, the pull-out performance, physical properties (i.e., density, thermal and acoustic insulation), short- and long-term properties (i.e., compressive, flexural, impact, and dynamic performance) of CFRC are reviewed. Existing modification methods (i.e., cementitious matrix and fibre surface modifications) to improve the bond and mechanical behaviour of CFRC and the practical application of CFRC in construction are presented. Future perspectives of CFRC studies are highlighted, including the validation of existing models (i.e., for the prediction of coir tensile strength as well as bond strength and total energy of CFRC), further investigations on long-term, seismic, fire performance of CFRC, and the use of coir fibre in geopolymer and coconut shell aggregate concrete towards practical application.